The French duty of vigilance law: A reference guide for the transposition of the corporate sustainability due diligence directive - Begüm Kilimcioğlu (Netherlands Quarterly of Human Rights)
In 2017, France became the first European Union Member State to adopt a duty of vigilance law ( loi relative au devoir de vigilance des sociétés mères et des entreprises donneuses d'ordre ) to address corporate human rights violations, with an extraterritorial effect. The Law was first of its kind and it was welcomed with much hope and excitement. However, although the Law carried great potential, the effective implementation and enforcement of the Law has been questionable. Nevertheless, the French experience carries great importance in the context of the new European Union Corporate Sustainability Due Diligence Directive which requires all Member States to enact similar laws. Therefore, the article aims to extrapolate from the French experience, so that the other Member States tasked with the obligation to enact similar laws in the context of the new Directive can benefit from the French experience.